The Group of Responsables “Aerodynamics (GoR AD)” : An Overview of activities and Success Stories - Mingione, G.; Coustols, E.; Monge, F.; Ven, H. van der; Richter, K.; Tormalm, M.; Cavalera, L.R.; Stefes, B.; Pagan, D.; Eliasson, P.; Mallet, M.; Gemma, R. (ICAS, 2022)
The GoR AD is active in initiating and organizing basic and applied research in aerodynamics and aerothermodynamics. Aerothermodynamics is closely related to space operations and flight through the earth’s atmosphere at very high speeds. Aerodynamics is a cornerstone of aeronautics and one of the primary design disciplines to determine the shape of the aircraft. Environmental issues are of great concern in aeronautics for civil aircraft and advanced aerodynamic design will have a significant impact on fuel consumption and the noise of aircraft. For military aircraft, the requirements of stealthy operation require new aircraft shapes to be considered and these shapes must be aerodynamically effective. The GoR AD remit covers aerodynamics, aeroacoustics, and aeroelasticity. The GoR AD is supporting a multi-disciplinary cooperation with the other GARTEUR Groups in areas where a mono-disciplinary approach is not meaningful. The Group is active in experimental, theoretical, analytical, as well as in numerical fields of aerodynamics to support the development of methods and procedures. Work in experimental areas is performed mainly to obtain valuable data for the validation of methods. Measurement techniques are developed and refined to increase accuracy and efficiency of experimental investigations. Other numerical studies give insight in the mechanisms of basic flow phenomena.